2009
DOI: 10.1248/bpb.32.1166
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Factor-3.ALPHA. Functions as an Accelerator of 3T3-L1 Adipose Differentiation

Abstract: Adipose differentiation is a complex process associated with coordinated changes in gene expression, cell morphology, and hormone sensitivity.1) Several transcription factors influence these processes, among which peroxisome proliferator activated receptor g (PPARg) and CCAAT/enhancerbinding protein (C/EBP) family have been extensively studied.2,3) C/EBPb and C/EBPd are induced in the early stage of adipocyte differentiation and then mediate the expression of PPARg and C/EBPa. [4][5][6] In contrast to C/EBPd, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 45 publications
(62 reference statements)
1
36
1
Order By: Relevance
“…A similar previous study revealed that HIF-1α binds to the hypoxia response element (HRE) in the IPAS promoter and induces the expression of IPAS (36). However, the stabilized form of HIF-1α does not affect the mRNA expression levels of HIF-3α in zebrafish embryos (35) and 3T3-L1 cells (37). This contradictory result may be due to the different cell lines or animal models used in the experiments.…”
Section: Regulation Of Hif-3α Expression At the Transcriptional Levelmentioning
confidence: 91%
See 2 more Smart Citations
“…A similar previous study revealed that HIF-1α binds to the hypoxia response element (HRE) in the IPAS promoter and induces the expression of IPAS (36). However, the stabilized form of HIF-1α does not affect the mRNA expression levels of HIF-3α in zebrafish embryos (35) and 3T3-L1 cells (37). This contradictory result may be due to the different cell lines or animal models used in the experiments.…”
Section: Regulation Of Hif-3α Expression At the Transcriptional Levelmentioning
confidence: 91%
“…This contradictory result may be due to the different cell lines or animal models used in the experiments. In addition to HIF-1α, Hatanaka et al (37) observed that the promoter activity of HIF-3α is specifically activated by HIF-2α. HIF-2α specifically binds to the sequence between -251 and -228 in the mHIF-3α promoter, which is essential in response to the activation of HIF-2α (37).…”
Section: Regulation Of Hif-3α Expression At the Transcriptional Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…An in vivo study in zebrafish embryos showed that overexpression of stabilized Hif-1␣ did not change Hif-3␣ mRNA levels, while it increased the expression of igfbp-1a mRNA, a known Hif-1 target gene (55). It was reported that Hif-2␣ mediated hypoxiainduced Hif-3␣ gene expression in murine 3T3-L1 cells (13). Augstein et al (1) showed that human HIF-3␣2 mRNA expression in human umbilical venous endothelial cells (HUVECs) is induced by hypoxia and this hypoxic induction involves both HIF-1␣, HIF-2␣, and other factors.…”
Section: Regulation Of Hif-3␣ Expression and Activitymentioning
confidence: 99%
“…These data suggest that IPAS/HIF-3␣4 negatively regulates tumor progression, likely by inhibiting HIF-1/2␣ activity. In cultured murine 3T3-L1 adipocytes, HIF-3␣ expression was induced during adipose differentiation and overexpression of HIF-3␣ at the early stage of differentiation accelerated 3T3-L1 adipocyte differentiation (13). Yamashita et al (52) disrupted the mouse Hif-3␣ locus using conventional gene knockout technology.…”
Section: Biological Function(s) Of Hif-3␣ Variantsmentioning
confidence: 99%